Negotiating professional identity formation in medicine as an 'outsider': The experience of professionalization for minoritized medical students - Rebecca L. Volpe; Margaret Hopkins; Jasmine Geathers; Candis Watts Smith; Yendelela Cuffee (Elsevier, 2021)
Introduction: While the U.S. general population is increasingly diverse, less than 15% of medical school matriculants are from minoritized backgrounds. Unfortunately, early evidence suggests that the process of professional identity formation (PIF) for minoritized medical students is more difficult than that of their counterparts. We conducted serial, semi-structured interviews to learn about the experiences of minoritized medical students. We asked: How do participants understand their personal identity, and how it fits in-or does not-with the medical culture? Methods: Participants were nine third-year medical students at a historically White and rural institution who self-identified as being members of at least one group that is historically underrepresented in medicine. Participants were interviewed one-on-one, twice, using a semi-structured guide with open-ended questions. Data were collected and analyzed simultaneously, using the principles of grounded theory. Results: Two themes speak to the process of PIF for minoritized students within the dominant cultures of medicine and medical education. First, participants experienced a complex push-pull of their personal identities: they pulled their personal identities into their professional development in positive ways, but also sometimes found it necessary to push their personal identities away and make them less salient in order to be successful. Second, this push-pull contributed to feelings of self-doubt and isolation. Conclusion: The results suggest that existing PIF frameworks are too simplistic with regard to the individual person. We therefore suggest that the social psychology concept of identity theory might appropriately complicate how we think about what the individual person brings to the PIF process.